Double-pyramid and Reverse Step Resistance Training Effectiveness on Physical Fitness Factors Among Elite Female Athletes - Hamid Arazi; Mozhgan Hassanzadeh; Ali Sayyah (Türk Spor ve Egzersiz Dergisi)
Due to the necessity of resistance training for athletes conditioning, loading patterns in order to improve training outcomes have received more attention in recent decades. Accordingly, the purpose of this study was to assess the impact of 8-week resistance training performed with double pyramid (DP) and reverse step (RS) systems on some physical fitness components of elite female athletes. 30 young female handball players are randomly assigned to the three groups of DP (age: 17.43±1.63 year, weight: 70.28±10.14 kg, fat percentage: 15.60±1.17), RS (age: 17.13±1.32 year, weight: 67.80±7.78 kg, fat percentage: 15.40±1.69), and control groups (age: 17.33±1.71 year, weight: 61.04±6.61 kg, fat percentage: 16.50±1.43). Training programs was performed for an eight-week, 3 sessions per week with loading pattern of DP or RS. Measurements including fat percentage, anaerobic power (RAST), agility (Illinois), Speed (45 meter sprint), strength (1RM), and muscle endurance (60% 1RM) are taken before and after the training course.After the training period, DP and RS groups had significant effects on the mean power, upper and lower body muscular endurance, fat percentage, agility and speed (p lt;0.05). Also, DP showed a significantly more increase in upper body strength compared to RS groups and RS showed a significantly more increase in lower body strength compared to DP groups (p lt;0.05). Also, comparison of DP and RS groups showed a significant difference in lower and upper body muscle endurance between the two groups (P lt;0.05); While, there was not a significant difference in anaerobic power, upper and lower body strength, fat percentage, speed, and agility tests between training groups. DP resistance training appears that to have more impact in improving anaerobic power, upper body strength and speed. While, RS ones showed a greater effect on increasing the lower body strength, muscular endurance, agility and fat percentage of female handball players.